The Academy & Football Program in Rondônia/BR - Lima, Danúbia; Melo, Iranira; Barbosa, Xênia; Oliveira, Rodrigo; Oliveira, Rodrigo (International Journal of Scientific Research and Management (IJSRM), 2022)
Football is recognized as a national passion of Brazilians, and described as the most practiced sport in the state of Rondônia. This text aims to problematize the development of the Academy & Football Program. Methodologically, this is a documentary research. The results indicated two projects approved in the Program: “From Terrão to The Banks of the University”, from the Federal University of Rondônia, and “Academy & Football in IFRO”, from the Federal Institute of Education, Science and Technology of Rondônia. It is considered that the Program may bring relevant contributions to the development of football in Rondônia, especially in the scope of research, continuing education and inclusion of women.